Kebugaran Jasmani dan Aktivitas Fisik Perspektif Hadis - Qonita Qonita; Mufidah Zahro; Annisa Aulia Syahfitri; Dwi Meutia Hasni (STIKes Ibnu Sina Ajibarang, 2025)
This paper explores the importance of physical fitness and physical activity from the perspective of the hadiths of Prophet Muhammad ﷺ. Islam, as a comprehensive religion, does not only emphasize spiritual aspects but also gives significant attention to the physical well-being of human beings. Physical fitness serves as a vital foundation for performing daily activities and acts of worship. Using a qualitative approach and library research, this study examines several hadiths that highlight the importance of maintaining bodily health, including physical activities such as running, swimming, archery, horseback riding, and wrestling. The study also discusses the educational values related to physical education that are embedded in these hadiths. It is found that physical activity in Islam not only provides physical benefits but also supports character development, discipline, and spiritual enthusiasm.